2010
DOI: 10.2353/ajpath.2010.091143
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Recruitment to the Inflamed Glomerulus Occurs via an αIIbβ3/GPVI-Dependent Pathway

Abstract: Recruitment of leukocytes to glomeruli is fundamental to the pathogenesis of many forms of glomerulonephritis. In a model of glomerulonephritis induced by in situ immune complex deposition, we previously observed that, in addition to leukocytes, platelets accumulate in glomerular capillaries, where they contribute to leukocyte recruitment. However, the mechanisms of platelet recruitment and the role of platelet-expressed P-selectin in leukocyte recruitment require further investigation. We used intravital micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 66 publications
3
65
0
Order By: Relevance
“…A similar implication of neutrophils and GPVI in platelet recruitment to the inflamed vasculature was previously shown in a model of glomerulonephritis induced by IV injection of an antibody to the glomerular basement membrane. 33 Consistent with our results, this previous study showed that neutrophil depletion and GPVI deficiency also reduced platelet accumulation in the inflamed glomerulus. Additionally, our intravital microscopy analysis revealed that neutrophils not only bind platelets directly but also unmask platelet-and GPVI-binding sites on the inflamed vessel wall.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A similar implication of neutrophils and GPVI in platelet recruitment to the inflamed vasculature was previously shown in a model of glomerulonephritis induced by IV injection of an antibody to the glomerular basement membrane. 33 Consistent with our results, this previous study showed that neutrophil depletion and GPVI deficiency also reduced platelet accumulation in the inflamed glomerulus. Additionally, our intravital microscopy analysis revealed that neutrophils not only bind platelets directly but also unmask platelet-and GPVI-binding sites on the inflamed vessel wall.…”
Section: Discussionsupporting
confidence: 93%
“…Our results therefore support the concept that the recruitment of platelets and neutrophils to sites of inflamed and/or injured vessels relies on 2-way cooperative interactions. 33,34 In this context, it is interesting to note that the extracellular matrix metalloproteinase inducer (EMMPRIN) was recently identified as a leukocyte counterreceptor for GPVI expressed by neutrophils. 35,36 When addressing the extent of endothelial damage during the early phase of the rpA reaction, we observed that the endothelial lining was generally preserved but displayed alterations in regions of neutrophil infiltration, thus suggesting that endothelial injury and/or endothelial retraction contribute to inflammatory bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental mouse models and patients with different types of glomerulonephritis platelets accumulate in the kidneys and/or platelet-derived factors are systemically elevated (21,22,105–108). Accordingly, some clinical studies (using only a small patient cohort, however) show beneficial effects of anti-platelet therapy in glomerulonephritis patients by reducing circulating platelet aggregates, albuminuria and/or glomerular filtration rate (109113) and anti-platelet drugs are indeed commonly prescribed in Japanese hospitals to patients with IgA nephropathy (114).…”
Section: Platelet-leukocyte Interactions In Pathologic Conditionsmentioning
confidence: 99%
“…Male mice subjected to unilateral ureteric ligation as previously described (23) were used between 16 and 18 wk of age, 12 wk after undergoing ureteric ligation. For intravital imaging, the posthydronephrotic kidney was prepared as previously described (20,23,42). Briefly, mice were anesthetized by initial i.p.…”
Section: Methodsmentioning
confidence: 99%